Retrospective chart review of minor tibial fractures in preschoolers: immobilisation and complications. Issue 6 (3rd April 2020) - Ferrier, Charlotte A; Schembri, Rachel; Hopper, Sandy M
Abstract : Objective: To compare the treatment practices (immobilisation vs non-immobilisation) of toddler fractures and other minor tibial fractures (both proven and suspected) in preschoolers, aged 9 months–4 years, and examine rates of ED re-presentations and complications. Methods: Retrospective chart review of presentations of minor tibial fractures, both proven (radiologically confirmed) or suspected (negative X-ray but clinical evidence of bony injury), in children aged 9 months–4 years presenting to a single tertiary level paediatric ED from May 2016 to April 2018. Data collected included treatment practices, subsequent unscheduled re-presentations (including reasons) and complications (defined as problems relating to the injury that required further active care). Results: A search of medical records yielded 240 cases: 102 had proven fractures (spiral, buckle or Salter-Harris II) and 138 were diagnosed with a suspected fracture. 73.5% of proven fractures were immobilised, predominantly with backslabs. 79% of suspected fractures were treated with expectant observation without immobilisation. Patients treated with immobilisation were more likely to re-present to ED compared with non-immobilised patients (18/104, 17.3% vs 9/136, 6.6% RR 2.62, 95% CI 1.23 to 5.58). 21 complications were seen in 19/104 (18.3%) immobilised patients. There were eight skin complications (complication rate of 7.7%) and 11 cast issues (complication rate of 10.6%). Two (1.5%) of the 136 patients had complications related to pain or limp. Pain was uncommonly found, although follow-up was not universal. Conclusion: In our centre, proven minor tibial fractures were more likely to receive a backslab, whereas for suspected fractures, expectant observation without immobilisation was performed. Although there is potential bias in the identification of complications with immobilisation, the study suggests that non-immobilisation approach should be investigated.